Frequency of HCV induced thrombocytopenia in Southern Punjab - Muhammad Usama Ur Rehman, Alisha Afzal, Mariam Mumtaz, Muhammad Zubair, Nouman Bhutta, Jalil Iqbal (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of HCV induced thrombocytopenia in Southern Punjab Conclusion: Present study showed a higher proportion of thrombocytopenia in cases of hepatitis C. Most of the infected patients were males and higher number of patients related to age group 20-45 years. No association of development of thrombocytopenia with age group, gender and diabetes mellitus was detected. Keywords: Liver cirrhosis, thrombocytopenia, hepatitis C, hepatocellular carcinoma